INTRODUCTION TO THE ETHNOPALEONTOLOGICAL STUDY OF PERUVIAN POPULAR CULTURE: FIRST PRELIMINARY CASES REPORTED - Villaseca-Robertson, Andrea (2021)
The work aimed was to report ethnopaleontological studies of popular culture and to report some cases of the traditional uses of fossils in the Peruvian people in the last century and today. Eight items of sociocultural infl uence were used: artistic or aesthetic, commercial or economic, legal concept, health, psychic and spiritual utilities, playful meaning, and symbolic or identity. Preliminary results mention the use of the fossils as magical objects, a physical manifestation of the spirits of the jungle such as “Tunche” or ritual objects on the shaman tables (ammonites, sea urchins, oysters, gastropods, etc.) and log fossils “kis-huar” interpreted as “sacred tree of the Inca.” In the archaeological context it refers to the Inca, Paracas, and Nasca cultures. Th is preliminary information shows us the need to design new specifi c research projects with multidisciplinary teams and local people.